Drawing : Statements by Artists : to accompany the All College Drawing Show March, 1985 ([S.l.] : [s.n.], 1985)
Jarvis, Don ; Boyd, Bruce ; Featherston, Bill ; Rees, Geoff ; Michener, Bob ; Burton, Dennis ; Beuys, Joseph ; Michener, Sally ; Ross, Rick ; Marden, Brice ; Bowden, Gary ; Peter, Fred ; Wertschek, John ; LeWitt, Sol ; Baker, Ted ; Johns, Jasper ; Anon ; etc.
Engels
boek